Meeting the Madwomen : Mental Illness in Women in Rhys's Wide Sargasso Sea, Hijuelos's Our House in the Last World, and Garcia's Dreaming in Cuban - Weaver, Melanie Boyter (East Carolina University, 2012)
This study seeks to examine the character of the madwoman in Caribbean literature in three novels: Jean Rhys's Wide Sargasso Sea, Oscar Hijuelos's Our House in the Last World, and Christina Garcia's Dreaming in Cuban. Four characters, Wide Sargasso Sea's Antoinette Mason, Our House in the Last World's Mercedes Santinio, and Dreaming in Cuban's Celia and Felicia Del Pino, all experience madness at some point in their lives, and each character dies at the end of her respective novel. What I seek to demonstrate is that their madness does not originate from one specific point, but comes from a variety of outer and inner influences. Each woman experiences abuse in her life, either by her mother, her husband, her husband's family, or some combination of the three.  On a larger theoretical scale, though, these women go mad because they are subject to interlocking systems of patriarchy and colonialism which undermine their ability to form an identity outside of the approval they are able to gain from the male figures of authority in their lives. In some cases, this male figure is her father, but upon his death, she transfers her sense of identity to her husband, which does not end well since her husband's abuse keeps him from being a stable or successful builder of identity. Additionally, each of these women has an identity connection with her natural surroundings, whether it is a garden, a house, or the sea, and exile from their safe places removes them from a location of stability on which they further based their sense of self, leaving them exiled from vibrant locations that celebrate their passion and femininity.   Each of these women experiences a singular event which exacerbates her circumstances to the point that it begins the mental spiral into madness and destructive behavior that results from it. I consider each woman's death and whether it is a triumph over madness or a defeat by madness. Finally, I consider how each character contributes to Caribbean feminist literary theory, either by creating a sense of outrage and inspiring action or by creating a sense of hope that a sense of self and peace can be attained despite the madness that often results from the abuses of the patriarchal system.
Keywords: Caribbean literature; Literature; Ecofeminism; Feminist literary theory; Postcolonial literary theory; Wide Sargasso Sea; Our house in the last world; Dreaming in Cuban; Rhys, Jean. Wide Sargasso Sea; Hijuelos, Oscar. Our house in the last world; García, Cristina, 1958- . Dreaming in Cuban; Mentally ill women in literature; Caribbean literature; Feminist literature